Kontribusi Pendidikan Dalam Pembangunan Ekonomi - Hastin Riva Nugraheni; Ninik Sudarwati (Program Studi Pendidikan Ekonomi, Universitas Flores, 2021)
The world of education is very closely related to development, it cannot be denied that the contribution of education to development is very large. Education is a way to progress and achieve social and economic welfare. This study provides an overview and results of research related to the contribution of education to economic development in Indonesia. This research method uses descriptive qualitative research methods used to collect information that is analyzed through observation of secondary data and observation of correlation between variables graphically. Data obtained from publications or documents from official institutions related to the field of education. The results of the study show that education in Indonesia, both in terms of quantity and quality, indirectly contributes to economic development in Indonesia.